2021
DOI: 10.1101/2021.11.05.464876
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delineating the genetic regulation of cannabinoid biosynthesis during female flower development in Cannabis sativa

Abstract: SUMMARYCannabinoids are predominantly produced in the glandular trichomes on cannabis female flowers. There is little known on how cannabinoid biosynthesis is regulated during female flower development. We aim to understand the rate-limiting step(s) in the cannabinoid biosynthetic pathway.We investigated the transcript levels of cannabinoid biosynthetic genes as well as cannabinoid contents during 7 weeks of female flower development. We demonstrated that the enzymatic steps for producing CBG, which involve ge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The results showed that CsMIXTA was significantly upregulated in week 5 and reduced thereafter ( Figure 1 B). CsMIXTA showed a similar expression pattern to that of the enzymes in the cannabinoid biosynthetic pathway [ 15 ]. We used a Pearson’s correlation matrix test to evaluate the relationship (positive and negative) between expression of MIXTA and other genes involved in cannabinoid synthesis with expression of cannabinoids across the full seven weeks of flower development ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that CsMIXTA was significantly upregulated in week 5 and reduced thereafter ( Figure 1 B). CsMIXTA showed a similar expression pattern to that of the enzymes in the cannabinoid biosynthetic pathway [ 15 ]. We used a Pearson’s correlation matrix test to evaluate the relationship (positive and negative) between expression of MIXTA and other genes involved in cannabinoid synthesis with expression of cannabinoids across the full seven weeks of flower development ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated that expression of cannabinoid biosynthetic genes peaked in weeks 4 or 5 [ 15 ]; CsMIXTA expression showed a similar pattern. It has been shown that trichomes produce most cannabinoids during the latter capitate-stalked glandular phase.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Liu et al, 2021). In recent work from this lab, this point was clearly established and further, the production of CBGA was identified as rate-limiting end point cannabinoid synthesis (Apicella et al 2022).…”
Section: Introductionmentioning
confidence: 93%
“…Hypothetically, beneficial microorganisms may be recognized as a potential threat by the plant which synthetizes phytochemicals as a defense response (Thakur et al, 2019;Balestrini et al, 2021). Supporting this, treatments with stress-related phytohormones significantly increase THC and CBD contents (Mansouri et al, 2009;Jalali et al, 2019;Apicella et al, 2021). Alternatively, promoting root growth and improving nutrient availability and uptake may allow for greater plant biomass and overall wealth, resulting in thriving secondary metabolism functions (Çakmakçı et al, 2020) and early maturation (Conant et al, 2017;Backer et al, 2019).…”
Section: Drug-type Marijuana and Hemp Cropsmentioning
confidence: 99%